2017
DOI: 10.1016/j.jnma.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Perceived to Influence the Decision for African Americans to Become Registered Organ Donors at the Department of Motorized Vehicles

Abstract: Background African Americans (AA) are a third as likely as Caucasians to become registered organ donors at the Department of Motorized Vehicles (DMV). The Department of Health and Human Services has set the goal that at least 50% of adults in each state are registered donors. Aims The purpose of this study was to explore the personal, behavioral and environmental factors associated with AA donor registration decision-making at the DMV. Methods Guided by the Social Cognitive Theory, 13 focus groups (n=100 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…There have been multiple studies conducted identifying barriers to AAs becoming registered organ donors (ROD); including mistrust in hospitals, influence of religious beliefs and spirituality, and lack of accurate information about the donation process and the associated financial aspects (57) . While there is a paucity of data regarding the factors associated with AAs positive decision to become RODs, studies have suggested that a desire to learn more about the donation process may be of benefit to RODs (8, 9) . Previously, we conducted a qualitative study based upon social cognitive theory utilizing 13 focus groups of AAs who had frequented a DMV in the past 3 months and made a ROD decision (8) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been multiple studies conducted identifying barriers to AAs becoming registered organ donors (ROD); including mistrust in hospitals, influence of religious beliefs and spirituality, and lack of accurate information about the donation process and the associated financial aspects (57) . While there is a paucity of data regarding the factors associated with AAs positive decision to become RODs, studies have suggested that a desire to learn more about the donation process may be of benefit to RODs (8, 9) . Previously, we conducted a qualitative study based upon social cognitive theory utilizing 13 focus groups of AAs who had frequented a DMV in the past 3 months and made a ROD decision (8) .…”
Section: Introductionmentioning
confidence: 99%
“…While there is a paucity of data regarding the factors associated with AAs positive decision to become RODs, studies have suggested that a desire to learn more about the donation process may be of benefit to RODs (8, 9) . Previously, we conducted a qualitative study based upon social cognitive theory utilizing 13 focus groups of AAs who had frequented a DMV in the past 3 months and made a ROD decision (8) . The goal of that study was to determine key indicators of AA DMV patrons’ decision whether to become a ROD or to not become a ROD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong body of evidence supports the use of active methods of recruitment to organ donation registers in other settings, specifically the Driving Motor Vehicles (DMV) offices in the U.S.A. Numerous studies have investigated how to improve sign-up rates in this setting, the majority of which have found success [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. The generalisability of these studies internationally however, is challenging, due to the unique nature of the DMV to the U.S.A.…”
Section: Discussionmentioning
confidence: 99%
“…Because the minority population is higher in OPO 1 than the OPO 2 and OPO 3, risk adjustment for race/ethnicity would give the OPO 1 a bump relative to the other local OPOs, even though the data demonstrate that the lower donation rates in OPO 1 are due to systematic lower donation rates among all racial/ethnic groups. In fact, risk adjustment would "excuse" OPO 1 for having disproportionately lower donation rates poor among Hispanics, which would require further OPO-level data on process measures from targeted education materials at Department of Motor Vehicles (DMVs), [30][31][32] to use of ethnicity-matched requestors for potential Hispanic donors, to hospital development and outreach in hospitals that care predominantly for minority populations,. Unfortunately, such data on different process measures within OPOs are currently not available to researchers.…”
Section: Data Challeng Ing Minorit Y S Tatus a S A Fixed Fac Tor Inmentioning
confidence: 99%